Determinants of Mobile Broadband Use in Developing Economies: Evidence from Nigeria - Maude Hasbi; Antoine Dubus (International Telecommunications Society (ITS), 2019)
Using micro-level data coming from household surveys over 5 years, from 2013 to 2017, we analyse what are the determinants of mobile broadband adoption in developing economies. We provide empirical evidence on the presence of a learning effect stemming from mobile money use, which by providing a higher experience in using mobile phone increases mobile broadband use. The ownership of a mobile phone is also positively correlated with mobile broadband use. However, for those not owning a mobile phone the ownership of an active SIM card is a prerequisite for using mobile broadband. We highlight that the population left behind is mainly composed of poor households living in rural areas.
Keywords: I30; O12; L50; L96; O55; 330; Mobile Broadband Use; Developing Economy; Inequality; Economic Growth